ANÁLISE DA PRODUÇÃO DE SAÚDE NO MUNICIPIO DE IRATI-PR, POR MEIO DO PROCESSO DE TRABALHO DAS AGENTES COMUNITÁRIAS DE SAÚDE - Aggio, Cristiane de Melo (2015)
To analyze the production of Health Primary Health Care (PHC) in Irati -PR through the work process of Community Health Workers ( CHW ) exploratory research was conducted , type of case study with a qualitative approach , triangulation data obtained the minutes of the city Council Health and interviews with CHWs and health secretaries of this municipality, which were subjected to content analysis. The characteristics of CHWs were similar to the national and international context. On objects of this work process, it stood out the low coverage of APS, prioritizing offer care to programmatic groups with chronic diseases, low access to technologies, longitudinality associated with long time agents in the profession and insufficient autonomy users in sustaining life. There was conflict between the goals of managers, agents and community, lack of material resources and non-material committed the care process and contributed to the invisibility of agents. The biomedical APS model persists and has not been the preferred contact of the population. It was concluded that various investments should be made to the effectiveness of APS, to the development and retention of agents and the promotion of community development, stressing the popular education.